Africanized honey bee (Apis mellifera) venom profiling: Seasonal variation of melittin and phospholipase A(2) levels - Ferreira Junior, Rui S. [UNESP]; Sciani, Juliana M.; Marques-Porto, Rafael; Lourenco Junior, Airton [UNESP]; Orsi, Ricardo de O. [UNESP]; Barraviera, Benedito [UNESP]; Pimenta, Daniel C. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Apis mellifera venom is comprised basically of melittin, phospholipase A(2), histamine, hyaluronidase, catecholamine and serotonin. Some of these components have been associated with allergic reactions, amongst several other symptoms. on the other hand, bee mass stinging, caused by Africanized honey bee (AHB), is increasingly becoming a serious public health issue in Brazil; therefore, the development of efficient serum-therapies has become necessary. In this work, we have analyzed the venom composition of AHB in Brazil through one year. In order to verify the homogeneity of this venom, one specific hive was selected and the correlation with climatic parameters was assessed. It was possible to perceive a seasonal variation on the venom contents of melittin and phospholipase A2. Moreover, both compounds presented a synchronized variation of their levels, with an increased production in the same months. This variation does not correlate or synchronize with any climatic parameter. Data on the variation of the AHB venom composition is necessary to guide future intra and inter species studies. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Apis mellifera; Africanized honey bee; Melittin; Seasonal variation; Natural peptides